The New Student Admission System in DKI Jakarta in 2020- 2021: Perceptions of Parents, Students, and Teachers - Nurlita, Dewi; Driana, Elin; Purwanto, Sigid Edy; Pertiwi, Linda (FKIP Universitas Lampung, 2024)
Abstract: The New Student Admission System in DKI Jakarta: Perceptions of Parents, Students, and Teachers. Objective: This qualitative research aims to explore the perceptions of parents, students, and teachers regarding PPDB in DKI Jakarta. Methods: This research adopts a phenomenological approach. Data collected through semi-structured interviews with 22 parents, 14 students, and 3 teachers at one junior high school in East Jakarta were analyzed using typological analysis. Findings: The research results indicate that the majority of informants are more in favor of using the distance between home and school rather than age as a selection criterion. Additionally, the majority of participants believe that students' academic achievements are the fairest selection criterion compared to others because it values students' diligence in learning and fosters a competitive spirit. Conclusion: A PPDB system that ensures the right to quality education is the aspiration of parents, students, and teachers. Therefore, efforts to equalize the quality and distribution of public schools are highly necessary to achieve the goals of PPDB. Keywords:admission of new student, junior high school, perception, selection criteria, phenomenology.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202408